2019
DOI: 10.1101/789107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation and Characterization of aRhizobiumBacterium Associated with the Toxic DinoflagellateGambierdiscus balechii

Abstract: 25Algae-bacteria associations are increasingly being recognized to be important in 26shaping the growth of both algae and bacteria. Bacteria belonging to order 27Rhizobiales are important symbionts of legumes often developing as nodules on plant 28 roots, but have not been widely documented in association with algae. Here, we 29 detected, isolated, and characterized a Rhizobium species from the toxic benthic 30dinoflagellate Gambierdiscus culture. The sequence of 16S rDNA showed 99% 31 identity with that of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…diazotrophs has yet to be directly documented, such a relationship may explain why some of the highest rates of DDN assimilation reported in the literature were measured in short, day-time experiments (Benavides et al, 2016;Sangsawang et al, As a number of potentially diazotrophic Alphaproteobacteria were abundant in the 16S rRNA community, notably Rhizobiales, it is surprising that these taxa were not equally abundant in the nifH Cluster I-III sequences. Rhizobiales contains many known diazotrophs that may associate with microalgae (Kim et al, 2014;Wu et al, 2019) and have been found in varying abundance in coral microbial communities (Lesser et al, 2018;Davey et al, 2007;Lema et al, 2012). While Rhizobiales have been proposed as possible diazotrophic coral symbionts (Lema et al, 2012), their role in coral N 2 fixation is still debated, particularly as some species contain only Cluster V nifH homologs and do not appear to fix nitrogen (Lesser et al, 2018;Wu et al, 2019).…”
Section: Diazotrophic Communitymentioning
confidence: 99%
See 1 more Smart Citation
“…diazotrophs has yet to be directly documented, such a relationship may explain why some of the highest rates of DDN assimilation reported in the literature were measured in short, day-time experiments (Benavides et al, 2016;Sangsawang et al, As a number of potentially diazotrophic Alphaproteobacteria were abundant in the 16S rRNA community, notably Rhizobiales, it is surprising that these taxa were not equally abundant in the nifH Cluster I-III sequences. Rhizobiales contains many known diazotrophs that may associate with microalgae (Kim et al, 2014;Wu et al, 2019) and have been found in varying abundance in coral microbial communities (Lesser et al, 2018;Davey et al, 2007;Lema et al, 2012). While Rhizobiales have been proposed as possible diazotrophic coral symbionts (Lema et al, 2012), their role in coral N 2 fixation is still debated, particularly as some species contain only Cluster V nifH homologs and do not appear to fix nitrogen (Lesser et al, 2018;Wu et al, 2019).…”
Section: Diazotrophic Communitymentioning
confidence: 99%
“…Rhizobiales contains many known diazotrophs that may associate with microalgae (Kim et al, 2014;Wu et al, 2019) and have been found in varying abundance in coral microbial communities (Lesser et al, 2018;Davey et al, 2007;Lema et al, 2012). While Rhizobiales have been proposed as possible diazotrophic coral symbionts (Lema et al, 2012), their role in coral N 2 fixation is still debated, particularly as some species contain only Cluster V nifH homologs and do not appear to fix nitrogen (Lesser et al, 2018;Wu et al, 2019). We found that Rhizobiales had low relative activity in both the tissue and skeleton (16S RNA:DNA < 1), and that the majority of Rhizobiales ).…”
Section: Diazotrophic Communitymentioning
confidence: 99%